Achieving enhanced ferromagnetism in ZnTbO nanoparticles through Cu co-doping. Issue 13 (September 2019) - Poornaprakash, B.; Subramanyam, K.; Vattikuti, S.V. Prabhakar; Pratap Reddy, M. Siva
Abstract: Magnetically polarized semiconductors are of significant interest in view of their application in spintronic devices. In this study, the microstructure and room temperature ferromagnetic characteristics of ZnO, Zn0.48 Tb0.02 O50, and Zn0.47 Tb0.02 Cu0.01 O50 nanoparticles (NPs) have been reported. The crystal structure and grain size of the samples were elucidated from comprehensive structural analyses; the results revealed a wurtzite crystal structure with dopant and co-dopant ions located at substitutional or interstitial sites in the ZnO host lattice. The nanoparticles sizes estimated from X-ray diffraction were confirmed by transmission electron microscopy. Diffuse reflectance spectra and the corresponding Kubelka-Munk plots suggested band gap quenching due to the inclusion of dopant ions. Magnetic measurements revealed diamagnetic character for the bare host material, while Zn0.48 Tb0.02 O50 and Zn0.47 Tb0.02 Cu0.01 O50 showed bending of hysteresis loops in the low magnetic field region and linear behavior within a certain range at higher fields, indicating ferromagnetic and paramagnetic behavior in the two regimes.